USING FISHBONE DIAGRAM STRATEGY ON STUDENTS’ WRITING ANALYTICAL EXPOSITION TEXT - Meilian, Karin; Natasha, Harum (Indonesian Journal of Integrated English Language Teaching, 2023)
This research was conducted based on students’ problems in writing, such as students have difficulty in developing ideas, students have difficulty in choosing correct grammar, and students have difficulty in writing sentences because lack of vocabulary. The main focus of this research is to investigate whether there is a significant difference on the students’ writing analytical exposition text before and after being taught by using the fishbone diagram strategy at the eleventh science grade students of Senior High School 15 Pekanbaru. The research design in this research was pre-experimental with one group pre-test and post-test design. The sample of this research was class the eleventh science 3 which consists of 35 students. The sample was taken by using purposive sampling technique. In collecting the data, the researcher used a writing test to determine the students’ writing skill of analytical exposition text. In analyzing the data, the researcher used the paired sample t-test formula calculated by using SPSS version 22. The results of the data analysis showed that the tobtained higher than ttable (2.179 > 2.032) with the significance level 0.05, and the degree of freedom (df) was 34 and the significant value was lower than the significant level (0.036 < 0.05). It means that Ho was rejected and Ha was accepted. So, there is a significant difference on the students’ writing analytical exposition text before and after being taught by using the fishbone diagram strategy. Keywords: Writing, Analytical Exposition, Fishbone Diagram.